KEMAMPUAN DECODING DAN ENCODING PESERTA DIDIK DALAM HASIL KARYA SENI MENGGUNAKAN MEDIA PHOTO STORY - Nurul Hidayah; Sri Nurlina; Prihantini (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research reports the problem that comes when art and culture learning subjects are related to drawing activities as a task given by educators for students, which makes a picture artwork with the determined theme, and then the results of the artwork are only collected without follow-up. It is due to the students’ low visual literacy. The research is conducted to determine students' visual literacy skills through visual thinking (encoding) and meaning reconstruction (decoding) in capturing photo story objects. The research method used is a descriptive analysis method with a qualitative research design. The research object is the high-grade students of SDN Sukasari. The instrument is an open questionnaire in the form of questions summarized in a google form and indicator sheet of visual literacy. Based on the research results and analysis, students' visual literacy skills through visual thinking (encoding) and meaning reconstruction (decoding) in capturing illustrated story objects have been seen and implementation for most students has been based on the indicators of visual literacy.